Divergent PCB organohalide-respiring consortia enriched from the efflux channel of a former Delor manufacturer in Eastern Europe - Praveckova, Martina; Brennerova, Maria V; Cvancarova, Monika; De Alencastro, Luiz Felippe; Holliger, Christof; Rossi, Pierre (Ecotoxicology and environmental safety, 2015)
Polychlorinated biphenyl (PCB) organohalide-respiring communities from the efflux channel of a former Delor manufacturer in Eastern Slovakia were assessed using metagenomic, statistical and cultivation-adapted approaches. Multivariate analysis of environmental factors together with terminal restriction fragment length polymorphisms of the bacterial communities in the primary sediments revealed both temporal and spatial heterogeneity in the distribution of microbial populations, which reflects the dynamic pattern of contamination and altered conditions for biodegradation activity along the channel. Anaerobic microcosms were developed from eight sediments sampled along the channel, where high concentrations of PCBs - from 6.6 to 136mg/kg dry weight, were measured. PCB dehalorespiring activity, congruent with changes in the microbial composition in all microcosms, was detected. After 10 months of cultivation, the divergently evolved consortia achieved up to 35.9 percent reduction of the total PCB concentration. Phylogenetic-analysis of the active Chloroflexi-related organohalide-respiring bacteria by partial sequencing of 16S rRNA genes in cDNA from microcosms with the highest PCB dechlorination activity revealed diverse and unique complexity of the populations. The predominant organohalide respirers were either affiliated with Dehalococcoides sp. and Dehalococcoides-like group (DLG) organisms or were composed of currently unknown distant clades of DLG bacteria. The present study should encourage researchers to explore the full potential of the indigenous PCB dechlorinating populations to develop effective bioremediation approaches that can perform the complete mineralization of PCBs in polluted environments.
Keywords: Bacteria, Anaerobic; geologické sedimenty; biodegradace; Polychlorinated Biphenyls; chemické látky znečišťující vodu; Hydrogen-Ion Concentration; multivariační analýza; Chloroflexi; halogenace; Water Pollutants, Chemical; monitorování životního prostředí; DNA bakterií; Multivariate Analysis; Halogenation; polychlorované bifenyly; RNA, Ribosomal, 16S; bakteriální RNA; DNA, Bacterial; Slovakia; Microbial Consortia; mikrobiální společenstva; Phylogeny; anaerobní bakterie; Cloning, Molecular; RNA, Bacterial; Environmental Monitoring; Sequence Analysis, DNA; Biodegradation, Environmental; Geologic Sediments; klonování DNA; Slovenská republika; sekvenční analýza DNA; fylogeneze; koncentrace vodíkových iontů; RNA ribozomální 16S